Dependence of internal pressure in low-rise buildings on aerodynamic parameters, defect features and background leakage. Issue 219 (December 2021) - Estephan, Johnny; Gan Chowdhury, Arindam; Elawady, Amal; Erwin, James
Abstract: Internal pressure is an important parameter in the estimation of wind effects on low-rise buildings. Cracks and defects located around building fenestrations, lead to air leakage that affects internal pressure. To assess this effect, an experimental study was conducted at the NSF NHERI Wall of Wind Experimental Facility at Florida International University on a full-scale building model. Defects of various sizes and shapes were modeled on one of the building walls. The effect of two simultaneous wall defects on the internal pressure was also investigated. In addition, an analytical procedure was used to predict the internal pressure caused by various wall leakage areas. Results of the analytical procedure were compared with those computed experimentally and reasonable agreement was observed for all leakage areas being considered. The experimental and analytical results showed that the internal pressure increases as the leakage area increases. The correlation between the external and internal pressures was evaluated for the walls and the roof, and the measured peak internal pressure coefficients were compared with those provided by ASCE 7–16 for enclosed and partially enclosed building configurations. It was shown that ASCE 7–16 peak internal pressure coefficients were underestimated for most of the leakage ratios being considered. Highlights: Cracks and defects in buildings lead to air leakage that affects the internal pressure. Full-scale wind-tunnel testing was conducted on a gable-roofed building with various defect features. Analytical analysis was performed to predict internal pressures. Internal pressure results were compared to ASCE 7–16 values for enclosed and partially enclosed buildings. Internal pressures increase with increasing defect size and exceed ASCE 7–16 suggested values.